Challenging quota market efficiencies: A case-study of Scotland (United Kingdom). (April 2021) - Cross, Helen
Abstract: Exploring fisheries access through the lens of market-based policies, this study investigates complexities surrounding the temporary accumulation or dispensation of quota units, which define rights to land catch in UK commercial sea-fishing. The study examines quota transaction behaviours from Scotland's ten industry membership groups, known as Producer Organisations (POs), by analysing their annual 'Production and Marketing Plans'. Integrating data from the government Fixed-Quota Allocation (FQA) database, and official 'quota-use' records, the analysis pieces together previously 'unknown knowledge' surrounding quota exchanges, in the UK offshore pelagic and whitefish sectors. Leasing and barter transactions are pervasive among those with access to quota, although a core-group of POs dominate pelagic opportunity. These dynamics suggest consolidation to a point of inefficiency, given the dependence of marginal POs in Scotland's rural areas upon marine fisheries capture and processing. Inclusive participatory scenario-modelling techniques may now offer equitable options, in a new era of fisheries management. Highlights: This study examines quota transaction behaviours in Scotland's commercial sea fishing industry. Data used comprises sectoral 'Production and Marketing Plans' and Marine Management Organisation (MMO) online records. All ten Producer Organisations in Scotland, reference extensive quota leasing and bartering (exchange) behaviour. These appear managed and regulated internally by the industry. Inclusive participatory scenario-modelling techniques may now offer equitable options, in a new era of fisheries management.